Effectiveness to promote weight loss maintenance and healthy lifestyle habits of a group educational intervention program in adults with obesity: IGOBE program. Issue 6 (November 2021) - Porca, Cristina; Rodriguez-Carnero, Gemma; Tejera, Cristina; Andujar, Paula; Casanueva, Felipe F.; Crujeiras, Ana B.; Bellido, Diego
Abstract: Background: To achieve sustainable weight loss and healthy lifestyle changes is a huge challenge in the fight against obesity. The objective of this study was to evaluate the effectiveness to promote weight loss maintenance and healthy lifestyle habits of a group educational intervention program, Group Intervention in OBEsity (IGOBE), compared with a usual care therapy to lose weight. Methods: Patients with obesity (n = 437; 18.5% men, 18–77 years and 40.4 ± 6.7 kg/m 2 ) were randomised into two groups to follow a prospective interventional real-life study: a control group (CG), treated with usual clinical practice, and an intervention group (IG), in which the patients participate in a group intervention program on healthy lifestyle habits with weekly sessions for six weeks, after which a re-evaluation was made at six months and at 12 months of follow-up. After finishing the study dropout rates were 44.6% in CG and 43.4% in IG. Anthropometric, dietetic habits and body composition data were analysed in both groups at the pre-intervention and post-interventions of the subjects by completer's analysis. Results: At 12 months of following IGOBE program, the IG achieved greater weight loss (–7.1% of the initial weight) than the CG, which exhibited a weight gain (3.0% of the initial weight). The body weight change induced in the IG was accompanied by a reduction in fat mass, particularly visceral fat and waist circumference. Relevantly, the IG adhered to a healthy dietary pattern and changed its eating habits, which correlated with the improvement in body weight. Conclusions: Intensive educational group treatment that induces a change of eating habits and adherence to healthy dietary pattern is more effective in a long-term to counteract obesity traits than a standard treatment performed individually. The IGOBE program could be a cost-effective practice in the clinical management of obesity.